O TESTE DE CAMINHADA DE SEIS MINUTOS COMO MÉTODO DE AVALIAÇÃO DA QUALIDADE DE VIDA EM CIRURGIA CARDÍACA - Dallazen, Fernanda; Steinke, Angela; Cruz, Dante T. D.; Windmöller, Pollyana; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo